Occurrence Of Parasitic Infections In Dogs In And Around Ludhiana, Punjab (India) (Applied Biological Research, 2012)
A total of 634 canines were sampled for both haematological (460) and  coprological (174) investigations at Small Animal Clinics, GADVASU,  Ludhiana, India during the year 2010. Examination of Giemsa stained peripheral blood smears exhibited 10.21% (47/460) haemoprotozoan  comprizing of Babesia gibsoni (8.26%), Hepatozoon canis (1.08%), B.  canis (0.65%) and Trypanosoma evansi (0.21%). B. gibsoni infection was significantly higher (p
Keywords: Canine; gastro-intestinal parasites; haemoprotozoa; Punjab